(untitled) (Research, Society and Development, 2020)
Congenital heart disease (CHD) are among the leading causes of death in early childhood. Its early diagnosis is essential for good prognosis. Treatment is complex and involves the association of drugs, whose selection considers age, clinical aspects and diagnosis. Was doing a review about treatments in newborns with heart disease. The research was conducted at Biblioteca Virtual de Saúde (BVS), CAPES, PUBMED and COCHRANE. Articles were selected using the following descriptors: cardiology, neonatology, adverse effect, intensive care. We found 71 articles in the BVS, CAPES 390, PUBMED 42 and COCRHANE 1, a total of 504 articles, but 39 duplicates were eliminated resulting in 465. At the end were included 10 articles in English, Portuguese and Spanish, selected by titles and abstracts. There are few studies evaluating the drugs safety in the treatment of newborns with CHD. The most commonly used drugs are digoxin, diuretics, β-blocker and catecholamines. Other drugs are prescribed, but less frequently. Drug association demonstrated benefit for patient’s clinical stabilization but increased the likelihood of drug interactions. Given the complexity and scarcity of the theme, this paper highlight the benefits and risks of CHD treatment in neonates.